Transfacet Minimally Invasive Transforaminal Lumbar Interbody Fusion With an Expandable Interbody Device—Part I: 2-Dimensional Operative Video and Technical Report. Issue 5 (20th May 2020) - Khalifeh, Jawad M; Dibble, Christopher F; Stecher, Priscilla; Dorward, Ian; Hawasli, Ammar H; Ray, Wilson Z
Abstract: BACKGROUND: Advances in operative techniques and minimally invasive technologies have evolved to maximize patient outcomes and radiographic results, while reducing morbidity and recovery time. OBJECTIVE: To describe the operative technique for a transfacet minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) as a proposed modification to the standard approach MIS-TLIF. METHODS: We present the case of a 72-yr-old man with left-sided lumbar radiculopathy. Preoperative imaging demonstrated degenerative lumbar anterolisthesis at L4-5, with associated canal and neuroforaminal stenosis. The patient underwent transfacet MIS-TLIF at L4-L5. We describe the preoperative planning, patient positioning, incision and dissection, pedicle screw insertion, transfacet approach to the working access corridor, discectomy, interbody device placement, fixation, and closure. RESULTS: The transfacet MIS-TLIF utilizes 3 key techniques to safely maximize surgical correction: (1) a limited bony resection based on the superior articular process, leaving the medial inferior articular process, lateral superior articular process, and rostral pars intact, providing a working bony corridor that protects the traversing and exiting nerve roots; (2) decortication and release of the contralateral facet joint to provide additional capacity for indirect decompression and provide the first point of osseous fusion; and (3) placement of an expandable interbody device that provides additional indirect decompression to the working side and contralateral foramen. CONCLUSION: The transfacet MIS-TLIF uniquely leverages a bony working corridor to access the disc space for discectomy and interbody placement. Transfacet MIS-TLIF is a feasible solution for lumbar spinal reconstruction to maximize direct and indirect decompression of the neuroforamina and central spinal canal in patients with lumbar degenerative diseases and low-grade spondylolisthesis.